Social work in malignant hematological diseases - Ancevska, Zaklina (Ревија за социјална политика/Journal of Social Policy, 2015)
Social Work in health began in 1900 at Massachusetts GeneralHospital in the US. At that time the way of treating patients wherepreviously the home care has been dominant, progressively started tochange to the gradual approximation of hospital treatment.Simultaneously with the changing of the site of treatment i.e. care,the professionals were beginning to understand that the conditions inwhich the patients lived and their personal problems are one of the factorsfor their illness and recovery.In that same hospital center, starts a home visiting program topatients by medical students and interns, so they could have theopportunity to know the patients, the way they live and in whichconditions they live in.